2011
DOI: 10.1080/01490400.2011.606778
|View full text |Cite
|
Sign up to set email alerts
|

Playing Our Way: Contributions of Social Groups to Women's Continued Participation in Golf

Abstract: This study builds upon research on leisure based social worlds and recent work identifying the potentially valuable roles of social groups in women's continued participation in recreation. This study is an ethnography of a group of women who regularly played golf. Data were analyzed using a grounded theory approach. The analysis suggested two overarching themes that explained persistence in golf for these women: connecting with group members and constructing a group culture. Importantly, the processes that fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
1
13
0
2
Order By: Relevance
“…When applied to golf, the constraint of interaction would include the difficulty of finding a golf partner. Research from Wood and Danylchuk (2011) suggests that persistence in golf is primarily driven by interpersonal factors such as connecting with group members and constructing a group culture. Interpersonal constraints would also include factors such as societal expectations, including gender expectations.…”
Section: Interpersonal Levelmentioning
confidence: 99%
“…When applied to golf, the constraint of interaction would include the difficulty of finding a golf partner. Research from Wood and Danylchuk (2011) suggests that persistence in golf is primarily driven by interpersonal factors such as connecting with group members and constructing a group culture. Interpersonal constraints would also include factors such as societal expectations, including gender expectations.…”
Section: Interpersonal Levelmentioning
confidence: 99%
“…The finding that neither the intensity nor the length of time of organisational involvement were associated with higher social connectedness scores was unexpected in the light of previous work (Stokowski, 2009;Wood and Danylchuk, 2011). There are at least three possible explanations for this: firstly, that heightened social connectedness precedes involvement in community sport; secondly, that social connectedness is heightened through involvement with community sport within a short period of time subsequent to joining and that this is not substantially increased further over time as a member; thirdly, that other or additional measures of involvement are required.…”
Section: Resultsmentioning
confidence: 56%
“…Previous research has found that when people develop social bonds with others in a particular setting, they are more likely to form a personal attachment to the setting or activity (Kyle and Chick, ; Funk and James, ; Wood and Danylchuk, ). Describing the concept as camaraderie, Filo et al .…”
Section: Discussionmentioning
confidence: 99%